1997
DOI: 10.1038/sj.onc.1201340
|View full text |Cite
|
Sign up to set email alerts
|

Somatic mutations in the human homologue of Drosophila patched in primitive neuroectodermal tumours

Abstract: The naevoid basal cell carcinoma syndrome (NBCCS) is an autosomal dominant disorder characterized by multiple developmental defects and cancer susceptibility, in particular to basal cell carcinomas (BCCs). Medulloblastomas, primitive neuroectodermal tumours (PNETs) arising in childhood, occur in about 3 ± 5% of NBCCS patients and a subset of PNETs was previously found with allelic imbalance at 9q22-q23, the region containing the gene for NBCCS (PTCH). We have analysed tumour DNA samples from 37 unrelated patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
82
0
3

Year Published

1998
1998
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(89 citation statements)
references
References 25 publications
2
82
0
3
Order By: Relevance
“…In keeping with the predisposition of NBCCS patients to developing the childhood brain tumour medulloblastoma, mutations of both PTCH and smoothened have been detected in sporadic medulloblastomas and other primitive neuroectodermal tumours (Pietsch et al, 1997;Ra el et al, 1997;Reifenberger et al, 1998;Vorechovsky et al, 1997a;Wolter et al, 1997). NBCCS patients develop the desmoplastic histological subtype of medulloblastoma, and while one study reported PTCH mutations exclusively in this subtype (Pietsch et al, 1997), mutations in classic medulloblastomas have also been described (Wolter et al, 1997).…”
Section: Smoothened and Bccsmentioning
confidence: 92%
“…In keeping with the predisposition of NBCCS patients to developing the childhood brain tumour medulloblastoma, mutations of both PTCH and smoothened have been detected in sporadic medulloblastomas and other primitive neuroectodermal tumours (Pietsch et al, 1997;Ra el et al, 1997;Reifenberger et al, 1998;Vorechovsky et al, 1997a;Wolter et al, 1997). NBCCS patients develop the desmoplastic histological subtype of medulloblastoma, and while one study reported PTCH mutations exclusively in this subtype (Pietsch et al, 1997), mutations in classic medulloblastomas have also been described (Wolter et al, 1997).…”
Section: Smoothened and Bccsmentioning
confidence: 92%
“…The binding of Hedgehog ligands to the PTCH receptor activates Gli signal transducers that then translocate into the nucleus to activate or repress transcription of its downstream genes. Aberrant Hedgehog signaling has been linked to the development of medulloblastomas, the common childhood tumors (Goodrich et al, 1997;Vorechovský et al, 1997;Shahi et al, 2008). Active Hedgehog-Gli signaling is also associated with gliomas (Shahi et al, 2008).…”
Section: Hedgehog-gli Signalingmentioning
confidence: 99%
“…Loss-of-function mutations in human PATCHED are associated with activation of the Hedgehog signal transduction pathway and promotion of a neoplastic state characterized by proliferating, undifferentiated cell populations (Hahn et al, 1996;Johnson et al, 1996). Of the children with Gorlin's Syndrome, which is caused by inherited mutations of PATCHED, 3-5% develop medulloblastoma (Vorechovsky et al, 1997). Inactivating mutations of PATCHED have also been found in sporadically occurring medulloblastoma (Raffel et al, 1997) and basal cell carcinoma, and mice heterozygous for targeted mutations of Patched, in which Shh targets are potentially upregulated, develop cerebellar tumors (Goodrich et al, 1997).…”
mentioning
confidence: 99%